Estimation of Reserve Funds for E-Banking Transactions using Operational Value-at-Risks - Halim, Nurfadhlina Abdul; Saputra, Moch Panji Agung (iora, 2022)
The â€œNew Normalâ€ state during the pandemic has made digital financial transactions important as an effort to reduce direct human interaction, to prevent the spread of the pandemic. The rate of financial transactions at banks has automatically increased, but in practice, several risks may occur about failed or incorrect digital transactions. Examples of digital transaction system risks are downtime and timeout services due to system failures, cyber-attacks, and system usage errors. These risks need attention from banking companies. One way to anticipate digital financial transaction failure happen is the readiness of a reserve fund that is used to cover the wrong amount of fund error in the bank's digital system. This research will discuss the estimation of operational reserve funds for digital banking financial transactions (e-banking) using the Operational Value-at-Risk (OpVaR) method, based on operational risk data for digital financial transactions to obtain the largest potential loss value from digital financial transaction activities at a bank. Based on calculations using the OpVaR method, it is known that the reserve fund required for the operational risk of digital financial transactions is IDR135,465,044,269.741. The results of this study show that the e-banking operational reserve fund is quite large due to the possibility of extreme losses. This provides a view to avoiding the worst risk of collapse due to an imbalance in the required reserve funds.